The Impact of Boycott Issues and Gold Price Volatility on PT X Stock Price - Santoso, Feby Indrawan; Fazaalloh, Al Muizzuddin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2026)
The long-standing political and military conflict between Israel and Palestine has had an impact on Indonesia’s economy. The conflict triggered large-scale boycott policies against several well-known brands. One of the affected companies was the products of PT X, resulting in declining sales which also led to a decrease in share value. This study aims to examine the effect of gold prices and boycott policies on the share price of PT X and to test whether there is a difference in the share price trend of X before and after the Boycott Issue of Israeli products. The researchers applied a quantitative approach through multiple linear regression testing and a difference test. The results show that the boycott issue has a significant negative effect on X’s share price. Meanwhile, gold prices have a significant positive effect on X’s share price. Furthermore, a difference was found in X’s share price before and after the boycott issue.